2021
DOI: 10.1111/ans.16613
|View full text |Cite
|
Sign up to set email alerts
|

Survival benefit of neoadjuvant chemotherapy and surgery versus surgery first for resectable colorectal liver metastases: a cohort study

Abstract: There is continued debate about the survival benefit of neoadjuvant chemotherapy in patients with resectable colorectal liver metastases (CRLM). In this retrospective cohort study, we compared the overall survival and progression‐free survival between patients who received neoadjuvant chemotherapy prior to CRLM resection with those who underwent CRLM upfront. A multivariable Cox proportional hazard regression analysis was performed to adjust for potential confounders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…With newly developed biological agents, further significant benefits were achieved. Almost 60% of populations were evaluated to have tumor response by combining oxaliplatin-based or irinotecan-based chemotherapy with such targeted agents[ 14 ]. In the present study, the 5-year PFS and OS rates were 25.2% and 54.0% for the irinotecan group, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…With newly developed biological agents, further significant benefits were achieved. Almost 60% of populations were evaluated to have tumor response by combining oxaliplatin-based or irinotecan-based chemotherapy with such targeted agents[ 14 ]. In the present study, the 5-year PFS and OS rates were 25.2% and 54.0% for the irinotecan group, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized controlled trial showed some benefit to disease-free survival but no benefit of overall survival if neoadjuvant ChT with FOLFOX was used in upfront resectable LM [132,133]. Other retrospective studies showed no benefits [134].…”
Section: Crclm-neoadjuvant Chtmentioning
confidence: 99%